Netrin-1 in Atherosclerosis: Relationship between Human Macrophage Intracellular Levels and In Vivo Plaque Morphology - Susanna Fiorelli; Nicola Cosentino; Benedetta Porro; Franco Fabbiocchi; Giampaolo Niccoli; Francesco Fracassi; Nicolò Capra; Simone Barbieri; Filippo Crea; Giancarlo Marenzi; Viviana Cavalca; Elena Tremoli; et al. (Biomedicines, 2021)
Netrin-1 is a laminin-like protein that plays a pivotal role in cell migration and, according to the site of its release, exerts both pro and anti-atherosclerotic functions. Macrophages, key cells in atherosclerosis, are heterogeneous in morphology and function and different subpopulations may support plaque progression, stabilization, and/or regression. Netrin-1 was evaluated in plasma and, together with its receptor UNC5b, in both spindle and round monocyte-derived macrophages (MDMs) morphotypes from coronary artery disease (CAD) patients and control subjects. In CAD patients, plaque features were detected in vivo by optical coherence tomography. CAD patients had lower plasma Netrin-1 levels and a higher MDMs expression of both protein and its receptor compared to controls. Specifically, a progressive increase in Netrin-1 and UNC5b was evidenced going from controls to stable angina (SA) and acute myocardial infarction (AMI) patients. Of note, spindle MDMs of AMI showed a marked increase of both Netrin-1 and its receptor compared to spindle MDMs of controls. UNC5b expression is always higher in spindle compared to round MDMs, regardless of the subgroup. Finally, CAD patients with higher intracellular Netrin-1 levels showed greater intraplaque macrophage accumulation in vivo. Our findings support the role of Netrin-1 and UNC5b in the atherosclerotic process.